PENGARUH PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR SISWA MATERI PANCASILA KELAS V SDS ISLAM AL-HUDA - Dwi Maulidina Putri; Tamba, Robenhart; Mailani, Elvi; Simanihuruk, Lidia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of snowball throwing cooperative learning assisted by flashcards on student learning outcomes on Pancasila as the state ideology in fifth grade at Al-Huda Islamic Elementary School. This study used aa quantitative approach with an experimental method using a one group pretest-posttest design. The sample in this study was all 30 fifth grade students. The results showed that before the treatment, the average student learning outcome score in the pretest was 54, which is considered low. After the treatment, the average student learning outcome score in the posttest increased to 86.83, which is considered good. The percentage of student learning completion also increased from 33.33% in the pretest to 93.33% in the posttest. Based on the results of the hypothesis test analysis using a paired sample t-test, a significance value (Sig. 2-tailed) of <0.001 was obtained at a significance level of α = 0.005. This indicates that the significance value is less than 0.05, so H0 is rejected and Ha is accepted. Thus, it can be concluded that the implementation of cooperative learning using flashcards has a significant effect on improving student learning outcomes.